Tradition und Diskurs Wandel als Möglichkeit islamischer Hermeneutik - Dziri, Amir (De Gruyter, 2023)
References to "Islamic tradition" are omnipresent in the general public sphere and in scholarship. However, there has not been much consideration of what actually constitutes Islamic tradition. This volume attempts to ground Islamic tradition in the theory of tradition in order to subsequently ask how this understanding can open up perspectives for an Islamic discourse theology.